Comparison of Resistance Values for Various Patrol Vessel Step Hull Geometry Variations Using Computational Fluid Dynamics (CFD) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
-AbstractThis study investigates the effect of stepped hull geometry variations on the hydrodynamic resistance of a patrol vessel operating in Morowali waters. Computational Fluid Dynamics (CFD) simulations were conducted to evaluate the resistance performance of an existing hull and eight stepped hull configurations at an operating speed of 30 knots. The parameters investigated include step spacing, spray strip angle, and spray strip configuration. The results demonstrate that the application of stepped hull geometry generally reduces total resistance compared to the baseline hull. The optimal configuration, Model S3 with a 1.0 m step spacing and a 60° spray angle, achieved the lowest resistance of 28,384.1 N, corresponding to a reduction of 7.34%. From an engineering perspective, this reduction is significant, as lower resistance directly contributes to improved fuel efficiency, extended operational range, and enhanced endurance of patrol vessels during maritime surveillance operations.
Keywords: CFD; Hydrodynamic resistance; Patrol vessel; Stepped hull; Resistance reduction